2016
DOI: 10.1017/s1479262116000095
|View full text |Cite
|
Sign up to set email alerts
|

Screening of cultivated and wildHelianthusspecies reveals herbicide tolerance in wild sunflowers and allelic variation atAhasl1(acetohydroxyacid synthase 1 large subunit) locus

Abstract: Acetohydroxyacid synthase (AHAS) inhibiting herbicides have played a significant role in effective weed control in the cultivation of sunflower since their discovery. The development of sunflower lines and hybrids resistant to these herbicides made their post-emergence application possible. In this study, wildHelianthusspecies were screened phenotypically for imidazolinone (IMI) and sulfonylurea (SU) resistance by herbicide spray and for allelic variations atAhasl1(Ahas1 large subunit) locus using simple seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Additionally, imidazolinone may control broomrape in areas of the world where this parasitic weed attacks sunflower (Alonso et al, 1998). Recently, Jacob et al (2016) reported that Helianthus praecox Engelm. & A.…”
Section: Biotic Traitsmentioning
confidence: 99%
“…Additionally, imidazolinone may control broomrape in areas of the world where this parasitic weed attacks sunflower (Alonso et al, 1998). Recently, Jacob et al (2016) reported that Helianthus praecox Engelm. & A.…”
Section: Biotic Traitsmentioning
confidence: 99%
“…The same tolerance was also obtained by EMS mutagenesis ( Gabard and Huby, 2001 ). Later, more populations of wild sunflowers resistant to AHAS herbicides were found (e.g., White et al, 2002 , 2003 ; Jacob et al, 2017 ). In addition, a new tolerance for imidazoline called Clearfield Plus ® was selected from an M2 population of 600,000 plants treated with EMS ( Sala et al, 2008a ).…”
Section: Plant Genetic Resources In Sunflowermentioning
confidence: 99%
“…The trait of most economical value to date is the CMS ( PET1 ) introgressed from the wild species H. petiolaris , which, along with restorer genes also incorporated from wild species, is responsible for the success of the sunflower hybrid seed industry. Dozens of examples of introgression of important traits have been published, and these include herbicide tolerance (Jacob et al, 2016) and disease and insect resistance, including disease resistance genes for rust (Chandler et al, 1986), downy mildew [ Plasmopara halstedii (Farl.) Berl.…”
Section: Case 1: Sunflowersmentioning
confidence: 99%